2005
DOI: 10.1007/s10633-005-7342-0
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Function Assessed by ERG Before and After Induction of Ocular Aspergillosis and Treatment by the Anti-fungal, Micafungin, in Rabbits

Abstract: This study was conducted to evaluate the effectiveness of a new antifungal drug, micafungin, and standard antifungal drugs against endophthalmitis induced in a rabbit by intravitreal injection of Aspergillus fumigatus, an important fungal pathogen. Effectiveness was evaluated by the preservation of b-wave amplitude at 72 h after injection of the fungus relative to the b-wave amplitude at baseline before any intravitreal injections. A 0.06 ml inoculum of 10(6) conidia of A. fumigatus was injected into the vitre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 38 publications
0
10
0
1
Order By: Relevance
“…This drug is used clinically as an antifungal agent and inhibits CYP46A1 with relatively high potency 40 . Although the safety of intravitreous injection of voriconazole on retinal function has been described in rabbits 41 , voriconazole transiently impairs bipolar cell function in monkeys 42 and is associated with retinal dysfunction in rats following repeated systemic administration 43 . Recently, the effects of repeated doses of voriconazole on the vision of healthy human subjects was investigated in a double-blind, placebo-controlled study 44 .…”
Section: Discussionmentioning
confidence: 99%
“…This drug is used clinically as an antifungal agent and inhibits CYP46A1 with relatively high potency 40 . Although the safety of intravitreous injection of voriconazole on retinal function has been described in rabbits 41 , voriconazole transiently impairs bipolar cell function in monkeys 42 and is associated with retinal dysfunction in rats following repeated systemic administration 43 . Recently, the effects of repeated doses of voriconazole on the vision of healthy human subjects was investigated in a double-blind, placebo-controlled study 44 .…”
Section: Discussionmentioning
confidence: 99%
“…In a similar study by Harrison et al, intravitreal injection of micafungin showed similar results to standard treatment with voriconazole and amphotericin B in A. Fumigatus keratitis, which was demonstrated by the maintenance of b-wave length in the ERG for all three antifungal therapies compared to the control group that received saline [ 60 ]. According to Hiraoka et al, topical application of micafungin (0.1%) was evaluated against the control group in uninfected rabbit eyes [ 63 ].…”
Section: Discussionmentioning
confidence: 88%
“…On the other hand, voriconazole has a disadvantage in maintaining retinal function compared to the other two substances, requires higher concentrations, and is considered more toxic than micafungin. Also, this protocol refers to the administration of only one intravitreal injection and not multiple [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Untreated, Aspergillus can cause diminution of the a-waves and b-waves on electroretinogram within 72 hours of infection in animal models. 10 Furthermore, active persistent infection can be difficult to differentiate from residual non-infectious inflammation; in these cases, repeat vitreous cultures can help guide further treatments.…”
Section: Discussionmentioning
confidence: 99%